Good old pap smear towers over the latest LBC for cervical screening: a study in a rural teaching institute of Tamil Nadu, India - Gowri Sankar, R.; Thamil Selvi, R.; Anbu Lenin, K.; Poornima, M. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Cervical cancer is the second most common cancer among Indian women and the fourth most frequent cancer in women across the globe. Though effective screening programmes are available, its role in effective prevention in a developing country like ours still remains an unanswered question and the probable reason behind this could be the difficulty in adopting liquid-based cytology (LBC) as the main screening program ahead of conventional pap smear (CPS). Aims and Objectives: This study was performed with an objective to analyse and interpret the samples by both CPS and LBC and to compare the both so as to find out the possibility of implementing LBC in a rural teaching institute of Tamilnadu like ours. Materials and methods: This was a prospective observational study which includes sample of 100 women who have attended the gynaecological outpatient department (OPD) of Vinayaka Missions Kirupananda, Variyar Medical College and Hospitals, Salem, Tamil Nadu. The slides were interpreted by two independent cytopathologists based on The Bethesda System and the results were analysed statistically. Results: The youngest patient was 19 years and the oldest was 68 years old. The most common age group in the study is 4th decade. The commonest clinical presentation was discharge per vaginum (PV). Screening time was less with LBC which also showed cleaner background compared to CPS. Other parameters like organisms and epithelial cell abnormalities were detected in both CPS and LBC. Conclusion: Even though LBC was few steps above CPS while considering the smear background and time taken to screen the slides, CPS still remains the better among the two in our setup taking into consideration the cost efficacy it provides which is the main factor for the population in our rural setup.